The discreditation of mad people within legal and psychiatric decision making: a systems theory approach - Munro, Nell (2008)
Luhmann defined social systems as structured around specific social codes, and comprised of the communications relating to that code. This thesis asks how the phenomenon of madness can be understood within this framework and argues that mad utterances are statements or acts which cannot be parsed according to any existing system of social or interpersonal meaning. The psy-disciplines transform these uncertain acts into stable meaning by defining them within a functionalist or pathological framework. These meanings are fragile because the operations of the psyche are socially invisible and so mad utterances have to be defined in relation to existing social systems of meaning. Mad utterances therefore generate uncertainty, which leads systems such as law and the economy to over-react to madness and discredit to a disproportionate degree what mad people have to say.